Self-reported physical activity and food intake patterns in schoolchildren aged 7-10 from public and private schools. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n5p497 - Maria Alice Altenburg de Assis; Filipe Ferreira da Costa (Universidade Federal de Santa Catarina, 2012)
Physical activity and diet are related to several health outcomes. The aim of this study was to analyze physical activity (PA) and diet patterns among Brazilian schoolchildren attending private or public schools. A cross-sectional, school-based study of elementary schoolchildren aged 7-10 years old (n = 2,936) was carried out in Florianopolis (southern Brazil). Self-reported food consumption and PA patterns were assessed by means of a questionnaire. A higher percentage of girls than boys met the recommendations for consumption of fruits and vegetables and limited their consumption of sweets and soft drinks. Boys reported higher PA levels than girls (P < 0.001). Children attending private schools were more likely to be in the highest tertile of PA (odds ratio = 1.53, 1.14-2.05) and 80% less likely to be active in commuting to school compared to public school students. Private schoolchildren were more likely to meet recommendations for fruits and vegetables, limit sweet consumption, report adequate meal frequency and no consumption of fast food or soft drinks. In summary, girls and private schoolchildren reported better eating patterns, while boys and private schoolchildren reported higher PA levels. Such results highlight the public school setting as a target for health promotion initiatives, along with other strategies, in developing countries.